2007
DOI: 10.3934/cpaa.2007.6.43
|View full text |Cite
|
Sign up to set email alerts
|

Semi-stable and extremal solutions of reaction equations involving the $p$-Laplacian

Abstract: We consider nonnegative solutions of −∆pu = f (x, u), where p > 1 and ∆p is the p-Laplace operator, in a smooth bounded domain of R N with zero Dirichlet boundary conditions. We introduce the notion of semistability for a solution (perhaps unbounded). We prove that certain minimizers, or one-sided minimizers, of the energy are semi-stable, and study the properties of this class of solutions.Under some assumptions on f that make its growth comparable to u m , we prove that every semi-stable solution is bounded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 28 publications
5
64
0
1
Order By: Relevance
“…Indeed, they showed that whenever n ≥ p + 4p/(p − 1), the function u(x) = log(|x| −p ) is a W 1,p (B 1 ) singular stable solution to (I.8), with Ω = B 1 and f (u) = p p−1 (n − p)e u . Stable solutions to (I.8) are known to be bounded in the optimal dimension range (I.9) also in the case of power-like nonlinearities and arbitrary domains, thanks to the result of Cabré and Sanchón [41], and in the radial case for every locally Lipschitz nonlinearity, as proved by Cabré, Capella, and Sanchón [33].…”
Section: Background and Known Resultsmentioning
confidence: 80%
“…Indeed, they showed that whenever n ≥ p + 4p/(p − 1), the function u(x) = log(|x| −p ) is a W 1,p (B 1 ) singular stable solution to (I.8), with Ω = B 1 and f (u) = p p−1 (n − p)e u . Stable solutions to (I.8) are known to be bounded in the optimal dimension range (I.9) also in the case of power-like nonlinearities and arbitrary domains, thanks to the result of Cabré and Sanchón [41], and in the radial case for every locally Lipschitz nonlinearity, as proved by Cabré, Capella, and Sanchón [33].…”
Section: Background and Known Resultsmentioning
confidence: 80%
“…Our first proposition establishes the analog of the classical results for (P λ ) in the Euclidean case. Using some ideas coming from Cabré and Sanchón [5] and Luo, Ye and Zhou [35] we prove the existence of a critical parameter λ * which is related with the resolvability of (P λ ).…”
Section: Proof Of Theorem 12mentioning
confidence: 92%
“…They proved that for every p > 1 and h(s) = e s , the extremal solution u * is an energy solution for every dimension and that it is bounded in some range of dimensions. For a more general non-linearity, Cabré and Sanchón [5] proved that every semi-stable solution is bounded for a explicit exponent which is optimal for the boundedness of semi-stable solutions and, in particular, it is bigger than the critical Sobolev exponent p * − 1. For general h(s) and p > 1 the interested reader can see [4,10,41,43] for more regularity results about the extremal solution.…”
Section: (12)mentioning
confidence: 99%
See 1 more Smart Citation
“…where f ∈ C 1 (R) and N ≥ 2. Over the last two decades stable solutions of nonlinear PDEs has received a lot of attention, especially in the case of problems driven by the p-Laplacian operator (see for instance [1,7,9,10,17,3,12,5,2,4,11,6,16]). However the case involving the mean curvature operator has remained almost inexplored.…”
mentioning
confidence: 99%